ANALISA PENERAPAN SERVER DEPLOYMENT MENGGUNAKAN KUBERNETES UNTUK MENGHINDARI SINGLE OF FAILURE - lilik Widyawati; Heroe Santoso; Hamdika Budiman (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
Distributed computing systems are one of the requirements in implementing server-based applications such as database servers and web servers in order to achieve high levels of performance. The problem that often occurs is failure on the server so that the performance of a server is disrupted, so it takes a deployment technique that can be used to provide a distributed system with high performance. Container-based virtualization is the choice for running distributed systems because of its lightweight architecture, fast performance and resource efficiency. One of the container-based virtualisations is the introduction of a distributed systems development tool called Kubernetes, which allows managing server deployments to provide high availability systems. The system development methodology used is the Network Development Life Cycle (NDLC). Of the 6 stages, only 3 stages are used, namely Analysis, Design, and Simulation Prototyping. The test or test scenario carried out is Ftp Deploy and Nginx Web Server so that it can maintain availability and the system is able to failover when a server failure occurs